Business Intelligence Applied to Corn Productivity (2020)
The following research was developed in the town of Tasco, Boyacá, with information retrieved from Colombia’s open data webpage on agricultural evaluation from 2011 to 2017. The town evidences that corn growing fields are changing the harvested area production, altering the performance rendered per semester. The cause of this problem is that the corn growth productivity varies each year, depending on the seeded area and the altitude of the terrain. One of the main objectives is to determine the connection between the production of the harvested corn area and the altitude in which it was harvested, using business intelligence tools. The investigation’s design was non-experimental, since previously established variables were not modified. In the same way, the investigation is based on a cross-sectional design, because the required data was retrieved in a single moment during the investigation. Using probability sampling, each element from the sample can be selected.